Enhanced efficacy of Escherichia coli nitroreductase/CB1954 prodrug activation gene therapy using an E1B-55K-deleted oncolytic adenovirus vector. - Chen, M; Green, N; Reynolds, G; Flavell, JR; Mautner, V; Kerr, D; Young, L; Searle, P (2004)
Viruses that replicate selectively in cancer cells constitute an exciting new class of anticancer agent. The conditionally replicating adenovirus (CRAd) dl1520, which lacks the E1B-55K gene, has elicited significant clinical responses in humans when used in combination with chemotherapy. A convergent development has been to use replication-defective viruses to express prodrug-activating enzymes in cancer cells. This can sensitize the cancer to prodrug, but depends upon achieving sufficient level, distribution and specificity of enzyme expression within the tumour. In this study, we have expressed the prodrug-activating enzyme nitroreductase (NTR) in the context of an E1B-55K-deleted adenovirus, CRAd-NTR(PS1217H6). We show that CRAd-NTR(PS1217H6) retains oncolytic growth properties, and expresses substantially more NTR than a comparable, replication-defective adenovirus. The combination of viral oncolysis and NTR expression results in significantly greater sensitization of SW480 and WiDr colorectal cancer cells to the prodrug CB1954 in vitro. In vivo, CRAd-NTR(PS1217H6) was shown to replicate in subcutaneous SW480 tumour xenografts in immunodeficient mice, resulting in more NTR expression and greater sensitization to CB1954 than with replication-defective virus. Combination therapy of CRAd-NTR(PS1217H6) with CB1954 reduced tumour growth from 13.5- to 2.8-fold over 5 weeks, and extended median survival from 42 to 81 days, compared with no treatment.